Mechanobiology-informed biomaterial and tissue engineering strategies for influencing skeletal stem and progenitor cell fate - Woodbury, Seth M.; Swanson, W. Benton; Mishina, Yuji (Frontiers in Physiology, 2023)
Skeletal stem and progenitor cells (SSPCs) are the multi-potent, self-renewing cell lineages that form the hematopoietic environment and adventitial structures of the skeletal tissues. Skeletal tissues are responsible for a diverse range of physiological functions because of the extensive differentiation potential of SSPCs. The differentiation fates of SSPCs are shaped by the physical properties of their surrounding microenvironment and the mechanical loading forces exerted on them within the skeletal system. In this context, the present review first highlights important biomolecules involved with the mechanobiology of how SSPCs sense and transduce these physical signals. The review then shifts focus towards how the static and dynamic physical properties of microenvironments direct the biological fates of SSPCs, specifically within biomaterial and tissue engineering systems. Biomaterial constructs possess designable, quantifiable physical properties that enable the growth of cells in controlled physical environments both in-vitro and in-vivo. The utilization of biomaterials in tissue engineering systems provides a valuable platform for controllably directing the fates of SSPCs with physical signals as a tool for mechanobiology investigations and as a template for guiding skeletal tissue regeneration. It is paramount to study this mechanobiology and account for these mechanics-mediated behaviors to develop next-generation tissue engineering therapies that synergistically combine physical and chemical signals to direct cell fate. Ultimately, taking advantage of the evolved mechanobiology of SSPCs with customizable biomaterial constructs presents a powerful method to predictably guide bone and skeletal organ regeneration.